THE EFFECT OF REAL EARNING REVENUE AND FUND OF THE ECONOMIC GROWTH WITH CAPITAL SHOP AS A MODERATING VARIABLE IN REGENCY / CITY OF ACEH PROVINCE, 2013-2015 - harun, harun (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to find out the influence of Regional Generated Revenue and Balanced Funds which consisted of Block Grant, Special Grant, and Profit Sharing Fund on Economic Growth with Capital Expenditure as moderating variable by analyzing APBN realization report which had been published through the official government website within three years (2013-2015). The research used comparative causal method. The samples were 51 districts/towns which APBN realization reports had been audited and published through official website. The data were analyzed by using descriptive analysis, classic assumption test, multiple linear regression analysis, hypothetic test, and residual test. The result of the research showed that Regional Generated Revenue, Block Grant, Special Grant had the influence Block Grant, Special Grant, and Profit Sharing Fund in Aceh Province, while Profit Sharing Fund did not. Capital Expenditure could not moderate the correlation of Regional Generated Revenue, Block Grant, Special Grant, and Profit Sharing Fund with Block Grant, Special Grant, and Profit Sharing Fund with economic growth. It could be proved through R2 value, Adjusted R2 value, and Fcount value and tcount value which decreased after moderating variable was added.